Curing agent, tunnel waste slag regenerated low-permeability material based on curing of multiple solid wastes and preparation method of tunnel waste slag regenerated low-permeability material

By using a curing agent combined with a bonding component composed of tetrasaccharide units and an industrial by-product, the problem of low utilization rate of tunnel slag waste and failure of traditional curing agents in high sulfate environments is solved, and efficient curing and excellent performance of tunnel slag waste regeneration low permeability materials are achieved.

CN119528528AActive Publication Date: 2025-02-28CHINA MCC17 GRP CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411732790.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize tunnel waste, resulting in waste of resources and environmental pollution. The traditional curing agent fails in a high sulfate environment, affecting the stability and strength of the material.

Method used

Using the bonding components composed of repeated tetrasaccharide units, a stable double helix structure is formed through hydrogen bonds and ion bonds. Combined with industrial by-products such as nickel-iron slag, blast furnace slag, calcium carbide slag, phosphogypsum, steel slag and peanut shell ash, a curing agent is prepared for curing tunnel waste slag regeneration and utilization of low permeability materials.

Benefits of technology

It significantly reduces the porosity and permeability coefficient of the soil, improves the material's permeability and mechanical properties, ensures that the material maintains stability and strength in high temperature and extreme environments, and is suitable for engineering applications with high permeability and high durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528528A_ABST
    Figure CN119528528A_ABST
Patent Text Reader

Abstract

The invention discloses a curing agent, a tunnel waste slag regenerated low-permeability material based on curing of various solid wastes and a preparation method of the tunnel waste slag regenerated low-permeability material, and belongs to the technical field of comprehensive utilization of tunnel waste slag. The curing agent comprises a gelling component, an alkali-activated component, a bonding component and a reinforcing component, wherein the ratio of the gelling component to the alkali-activated component to the bonding component to the reinforcing component is (6-7): 1: (0.45-0.7): (1.6-1.7). Materials prepared from the curing agent comprise tunnel waste slag, the curing agent and water. The binding component and the multi-element solid waste synergistically improve the anti-permeability performance of the material, a three-dimensional network formed by the binding component and hydration products of the blast furnace slag and the ferronickel slag jointly act, tiny pores in the material are filled, and the porosity is reduced; and the material has higher thermal stability and gelling capacity, and is more resistant to acid and alkali environments, so that better support and stability can be provided when solid wastes are mixed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of comprehensive utilization of tunnel waste, and more specifically, relates to a curing agent, a tunnel waste regeneration low-permeability material based on solidification of various solid wastes, and a preparation method thereof. Background Art

[0002] Roads are the link between people's exchanges and communication, while tunnels are the key channels that cross mountains and promote spiritual and material cultural exchanges between different regions. With the gradual development of the economy in the western region, transportation construction has become increasingly important, and tunnel projects have been rapidly promoted, resulting in a large amount of tunnel waste. Due to the lagging management model and the limitations of tunnel waste itself, the utilization rate of these wastes is only about 20%, and most of the waste has not been effectively utilized and needs to be centrally piled up for disposal. This not only occupies a large amount of land, causing a great waste of resources and space, but also due to the loose accumulation and difficulty in soil formation, it may cause disasters such as soil erosion and mudslides. In addition, due to the differences in mineral resources in the areas where the tunnels are located, the waste may contain harmful ions. Long-term storage may cause excessive levels of iron, manganese, nickel, beryllium and other elements in groundwater or soil, causing environmental pollution. Therefore, how to effectively and comprehensively utilize tunnel waste in the western region and optimize resource allocation has become a key issue that needs to be solved urgently.

[0003] Take the Fenghuangshan Tunnel of the Qingshuiyi to Zhonghe section of the G30 Lianhuo Expressway as an example. The project is located in Jinya Town, Yuzhong County, Lanzhou City. It is designed as a long tunnel with left and right separated double holes. It is 3,945 meters long and belongs to the special long tunnel of the highway. The maximum burial depth is 180 meters. A large amount of tunnel waste soil was generated during the construction process. These waste soils show unstable strength when they come into contact with water, and are rich in sulfates, with the engineering characteristics of saline soil. Due to the concentrated and long-lasting rain in July and August in Lanzhou, Gansu, long-term water accumulation is prone to occur at the construction site. In this environment, traditional lime-based solidified soil is very easy to become unstable, resulting in serious threats to the safety and stability of the roadbed. In order to deal with this problem, the construction site usually adopts the anti-seepage measure of "two cloths and one membrane", that is, laying two layers of geotextiles and one layer of geomembrane in the roadbed. However, although this traditional treatment method has achieved an anti-seepage effect to a certain extent, it has greatly increased the construction cost and construction period. In addition, geosynthetics such as geomembranes and geotextiles are plastic products that are difficult to degrade naturally, causing long-term damage to the ecological environment and urgently requiring technological innovation and improvement.

[0004] After searching, patent CN101182139A discloses a masonry cement with high strength and water retention, in which an organic thickener is added, and the organic thickener is a polysaccharide such as starch or modified starch, starch ether, agar, gum arabic, soybean gum, guar gum and its derivatives, xylan, xanthan gum, etc. However, biological gums such as xanthan gum and guar gum are easily degraded or lose viscosity at high temperatures, affecting the structural strength.

[0005] Patent CN104478361A discloses a method for pre-treating industrial solid waste, which uses industrial tail gas to treat solid waste, and the obtained red mud-based polymer gelling material selects one or more of biopolysaccharides, phosphates, porous materials, silicates, organic polymer heavy metals and alkaline solidification / stabilization components as pollution factor solidifiers, but the patent does not design the treatment of high sulfate and strong sulfate soils. The technology disclosed in the patent is mainly used for the stabilization of heavy metal-contaminated solid waste, and does not involve the inhibition or solidification mechanism of high-concentration sulfate ions. The high sulfate leaching problem in tunnel waste may cause material expansion and damage, affecting the solidification effect. Summary of the invention

[0006] 1. Problem to be solved

[0007] In view of the problem that the existing curing agent is not suitable for tunnel waste, the first object of the present invention is to provide a curing agent, which can significantly reduce the porosity of the soil body, reduce the permeability coefficient, and is suitable for an environment with high impermeability and high durability;

[0008] The second purpose of the present invention is to provide a tunnel waste slag regeneration low-permeability material based on the solidification of various solid wastes and a preparation method thereof. The prepared material can significantly reduce the porosity of the soil and reduce the permeability coefficient. The prepared material has sufficient strength and excellent water stability.

[0009] 2. Technical solution

[0010] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0011] The first object of the present invention is to provide a curing agent for curing tunnel waste and recycling low permeability materials, which includes a gelling component, an alkali-activated component, a bonding component, and a reinforcing component, wherein the mass ratio of the gelling component, the alkali-activated component, the bonding component, and the reinforcing component is: (6-7): 1: (0.45-0.7): (1.6-1.7), the bonding component is composed of repeated tetrasaccharide units, and a stable double helix structure is formed by hydrogen bonds and ionic bonds, and the tetrasaccharide units include D-glucose, D-glucuronic acid, D-glucose and L-rhamnose connected in sequence, and the four sugars are connected by oxygen bridges to form a long chain structure, and the stability is enhanced by the interaction of hydrogen bonds and ionic bonds. Specifically, the D-glucose and D-glucuronic acid are connected by β-1,4 glycosidic bonds, and the L-rhamnose and D-glucose are connected by α-1,3 glycosidic bonds, forming a cyclic tetrasaccharide unit. According to the above connection relationship, the molecular formula of the bonding component is (C6H 10 O5) n (C6H 10 O5) m (C5H 10 O4) k , n, m and k in the molecular formula represent the degree of polymerization of the molecular chain, (C6H 10 O5) n represents the glucose (Glc) unit, (C6H 10 O5) m represents the glucuronic acid (GlcA) unit, (C5H 10 O4) k It represents a rhamnose (Rha) unit, wherein the values ​​of n, m and k are 20-25, and n, m and k satisfy 2:1:1. The specific degree of polymerization can be designed according to actual needs.

[0012] Furthermore, a common preparation method of the bonding component is to synthesize polysaccharides through an enzyme-catalyzed reaction, and the specific steps are as follows:

[0013] S1. Prepare raw materials: ensure that the ratio of glucose (Glc), rhamnose (Rha) and glucuronic acid (GlcA) is 2:1:1;

[0014] S2. Catalytic reaction: Select transglycosidase and mix glucose, rhamnose and glucuronic acid in proportion to promote the formation of glycosidic bonds between them.

[0015] The enzyme-catalyzed reaction has the following key steps: dissolving glucose, rhamnose and glucuronic acid in water, adding the transglycosidase in an amount of 0.1wt%-0.8wt% of the total dry weight of the polysaccharide, adjusting the pH value to a suitable enzyme-catalyzed reaction range, generally pH 5.5-7.0; adding the transglycosidase to catalyze the reaction at a temperature of 30°C-50°C, wherein the enzyme catalyzes the formation of glycosidic bonds between glucose, rhamnose and glucuronic acid; during the reaction, high performance liquid chromatography (HPLC) can be used to monitor the formation of glycosidic bonds and the growth of polysaccharide chains;

[0016] S3. Purification and molecular weight control: The reaction time is set to 48h-72h. After the reaction is completed, dialysis, gel permeation chromatography (GPC) or ultrafiltration technology is used to remove unreacted monosaccharides, enzymes and by-products to obtain pure bonding components;

[0017] S4. Purification and molecular weight control: Drying and storage: The purified polysaccharide solution is freeze-dried to obtain a powdered bonding component, which can be stored for a long time and used for the subsequent preparation of a curing agent.

[0018] Furthermore, the added amount of the bonding component is 0.6%-0.8% of the dry mass of the tunnel waste.

[0019] Preferably, the average molar mass of the bonding component is not less than 500,000 g / mol, and the particle size is not greater than 0.15 mm.

[0020] Furthermore, the mass ratio of the gelling component to the alkali-activated component is (6-7):1, and the gelling material is composed of nickel-iron slag and blast furnace slag, and the mass ratio of the nickel-iron slag to the blast furnace slag is (2-3):1.

[0021] Preferably, the specific surface area of ​​the nickel-iron slag is not less than 400m 2 / kg, the water content is less than 1%; the density of the blast furnace slag is not less than 2.8g / cm 3 , with a specific surface area of ​​not less than 400m 2 / kg, water content is less than 1%.

[0022] Furthermore, the alkali-activated material is composed of carbide slag and phosphogypsum, and the mass ratio of the carbide slag to the phosphogypsum is 10 / 1-11 / 1.

[0023] Preferably, the specific surface area of ​​the carbide slag is not less than 200 meshes, the calcium hydroxide content is not less than 60%, and the water content is less than 1%; the specific surface area of ​​the phosphogypsum is 400m 2 / kg-500m 2 / kg, soluble phosphate content 1%-2%, water content less than 1%.

[0024] The bonding component used in this patent has a unique molecular structure, and its molecules are composed of repeated tetrasaccharide units (glucose, rhamnose and glucuronic acid), forming a stable double helix structure through hydrogen bonds and ionic bonds. The formation of the double helix structure reduces the free energy of the molecular system, making the bonding component difficult to decompose at high temperatures, and not affecting the strength at low temperatures, showing excellent thermal stability. Its structure can remain stable over a wide temperature range (from freezing conditions to above 100°C), not only adapting to high temperature conditions, but also maintaining high strength and performance stability under low temperature environments. Compared with agar, although agar has better heat resistance, its strength in low temperature environments is lower, and its ability to adapt to extreme temperature difference environments is not as good as the bonding component of the present invention. Therefore, the bonding component of the present invention can maintain its strength and stability under more harsh conditions in engineering applications. In addition, the bonding component can quickly form a gel at a lower concentration, and the formed gel structure is firm, showing excellent mechanical strength and long-term stability. Compared with other biological glues (such as guar gum), the bonding component has a stronger gel ability and shows higher stability in both acidic and alkaline environments. This property enables the bonding component to provide better support and stability when mixed with solid waste materials, thus having significant advantages in complex engineering environments.

[0025] Furthermore, the added amount of the reinforcing component is 13%-25% of the dry mass of the tunnel waste slag, and the reinforcing component is peanut shell and steel slag, wherein the mass ratio of peanut shell to steel slag is (3-2): (7-3).

[0026] Preferably, the peanut shell ash has a fineness of no more than 30%, a silicon dioxide content of more than 90%, and a water content of less than 1%; the steel slag has a specific surface area of ​​400m 2 / kg-500m 2 / kg, water content is less than 1%.

[0027] The second object of the present invention is to provide a tunnel waste regeneration low permeability material based on the solidification of various solid wastes, the material includes tunnel waste, a curing agent and water, the curing agent includes a gelling component, an alkali excitation component, a bonding component, and a reinforcing component, wherein the bonding component is composed of repeated tetrasaccharide units, forming a stable double helix structure through hydrogen bonds and ionic bonds, and the tetrasaccharide units include D-glucose, D-glucuronic acid, D-glucose and L-rhamnose connected in sequence, and the four sugars are connected by oxygen bridges to form a long chain structure, and the stability is enhanced by the interaction of hydrogen bonds and ionic bonds. Specifically, the D-glucose and D-glucuronic acid are connected by β-1,4 glycosidic bonds, and the L-rhamnose and D-glucose are connected by α-1,3 glycosidic bonds to form a cyclic tetrasaccharide unit. According to the above connection relationship, the molecular formula of the bonding component is (C6H 10 O5) n (C6H10 O5) m (C5H 10 O4) k , n, m and k in the molecular formula represent the degree of polymerization of the molecular chain, (C6H 10 O5) n represents the glucose (Glc) unit. (C6H 10 O5) m represents the glucuronic acid (GlcA) unit. (C5H 10 O4) k It represents a rhamnose (Rha) unit, wherein the values ​​of n, m and k are 20-25, and n, m and k satisfy 2:1:1. The specific degree of polymerization can be designed according to actual needs.

[0028] The dry mass ratio of the tunnel waste slag to the curing agent is 1:(0.08-0.1), and the moisture content of the tunnel waste slag is controlled at 15%-16%.

[0029] Furthermore, 80%-85% of the tunnel waste is loess, and 15%-20% is basalt rock fragments. According to the liquid limit and plastic limit combined determination test, the liquid limit is 29.2%, and the plastic limit index is 10.9, which is low plastic clay.

[0030] Furthermore, the total amount of soluble salt in the tunnel waste is 3.0-3.1%, the total amount of chloride ions is 0.20-0.30%, and the concentration of sulfate ions is 1.10-1.30%, which belongs to strong sulfate soil. 2- ) / c(Cl - )>2.

[0031] Furthermore, the sulfate ion leaching concentration of the tunnel waste is 1701 mg / L-1758 mg / L.

[0032] The present invention also provides a method for preparing the tunnel waste slag regeneration low-permeability material based on the solidification of various solid wastes, comprising the steps of:

[0033] Tunnel waste, curing agent and water are mixed and then molded and cured in sequence to obtain roadbed filling.

[0034] Furthermore, due to insufficient water temperature, the adhesive components are difficult to fully dissolve, and particles are easily agglomerated in the liquid, resulting in uneven dissolution. Therefore, when the water is boiled to 100°C, the bio-glue material is added in advance and stirred with a liquid mixer until it is completely dissolved. At the same time, before adding water, ensure that the water temperature is maintained at around 90°C.

[0035] Furthermore, in the forming step: the forming method is static compaction method.

[0036] Furthermore, in the curing step: constant temperature and humidity curing is adopted, the curing temperature is 23±1°C, the relative humidity is 98%, and the curing age is set to 7 days and 28 days.

[0037] The components of this patent form a multi-level and multi-dimensional solidification system through chemical reactions and physical effects. The gelling effect of nickel-iron slag and blast furnace slag is strengthened by the alkali-induced reaction of carbide slag and phosphogypsum. The three-dimensional network structure provided by the bonding component further enhances the bonding and moisture retention of the filler, while the reinforcing effect of peanut shell ash and steel slag provides the filler with better structural stability and strength. The above-mentioned curing agent is used in the solidification of tunnel waste. The activation of rock cuttings in tunnel waste must rely on efficient alkali-induced reaction. This patent activates rock cutting components through alkali-induced reaction, inhibits the expansion and leaching of sulfate ions, and enhances the performance of composite gelled products. It provides a curing technology that is more in line with the characteristics of tunnel waste, and has significant technical advantages and applicability.

[0038] The material prepared by the above method has effectively improved anti-permeability and mechanical properties. Its performance parameters are: the permeability coefficient after 28 days is 3.19×10 -8 -7.15×10 -9 m / s, and the unconfined compressive strength reaches 13.05MPa.

[0039] 3. Beneficial effects

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) The curing agent of the present invention is composed of repeated tetrasaccharide units, and the bonding component of the stable double helix structure formed by hydrogen bonds and ionic bonds cooperates with the multi-solid waste to improve the anti-permeability performance of the material. The three-dimensional network formed by the bonding component works together with the hydration products of blast furnace slag and nickel-iron slag to fill the tiny pores in the material and reduce the porosity; and it has higher thermal stability and gel ability, and is more resistant to acid and alkali environments, so that it can provide better support and stability when mixing tunnel waste;

[0042] (2) The material of the present invention significantly improves the unconfined compressive strength of the tunnel waste slag recycling material by optimizing the curing agent formula. Under the action of the alkali-activated component, the nickel-iron slag and the blast furnace slag generate a gelled product through a volcanic ash reaction; the active calcium, aluminum, and silicon elements released by the enhancing component further promote the hydration reaction; the bonding component effectively improves the density and mechanical properties of the material by forming a network structure with the hydration product;

[0043] (3) The present invention uses a double helix structured bonding component as a curing agent. The bonding component can effectively resist the problem that during the curing process of tunnel waste, sulfate ions change the pH value of the aqueous solution, thereby affecting the cementing reaction and the curing process, through its hydrogen bond and ionic bond network structure, and maintain the strength and stability of the material;

[0044] (4) The present invention uses tunnel slag as the main material, and utilizes the rock fragments in the tunnel slag to participate in chemical reactions in an alkaline environment to generate additional cementitious products, which are used as aggregates to improve the density and compressive strength of the material, thereby further enhancing the performance of the material;

[0045] (5) The present invention realizes the recycling of resources by utilizing industrial byproducts such as nickel iron slag, blast furnace slag, carbide slag, phosphogypsum, steel slag and peanut shell ash, has good environmental friendliness, and reduces the cost of raw materials;

[0046] (6) The curing agent components of the present invention are diverse and synergistic, and can adapt to different construction environments and material requirements, especially in projects requiring high impermeability and high durability;

[0047] (7) The present invention adopts environmentally friendly materials such as peanut shell ash and industrial waste, which reduces the use of traditional materials such as cement and meets the requirements of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments, but it should be understood that these drawings are designed only for explanation purposes and are not intended to limit the scope of the present invention. In addition, unless otherwise specified, these drawings are intended only to conceptually illustrate the structural configurations described herein and are not necessarily drawn to scale.

[0049] Figure 1 This is an electron microscope image of the hydration product of the present invention. DETAILED DESCRIPTION

[0050] The following detailed description of exemplary embodiments of the present invention refers to the accompanying drawings, which form a part of the description, and in which exemplary embodiments of the present invention that can be implemented are shown as examples. Although these exemplary embodiments are described in sufficient detail to enable those skilled in the art to implement the present invention, it should be understood that other embodiments can be implemented and various changes can be made to the present invention without departing from the spirit and scope of the present invention. The following more detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but is only for the purpose of illustrating and not limiting the description of the characteristics and features of the present invention, so as to propose the best mode for performing the present invention and to enable those skilled in the art to implement the present invention. Therefore, the scope of the present invention is limited only by the appended claims.

[0051] It should be understood that the following text is only used to describe one or several specific embodiments of the present invention, and does not strictly limit the scope of protection of the specific claims of the present invention. As used herein, the terms "parallel" and "perpendicular" are not limited to their strict geometric definitions, but include tolerances for reasonable and inconsistent machining or human errors.

[0052] The chemical compositions of the components used in this application are shown in Table 1.

[0053] Table 1 Chemical composition and content of each component in this application (wt%)

[0054] <![CDATA[Al2O3]]> <![CDATA[SiO2]]> MgO CaO <![CDATA[Cr2O3]]> <![CDATA[Fe2O3]]> C <![CDATA[SO3]]> <![CDATA[P2O5]]> Ferronickel slag 27.63 28.83 23.43 4.45 8.88 4.20 - - - Blast furnace slag 15.8 27.56 7.51 42.19 - - - 2.88 - Carbide slag 1.33 1.41 - 95.2 - 0.12 - 0.34 - Phosphogypsum 0.75 7.88 - 38.53 - 0.85 - 49.2 1.39 Steel slag 2.20 12.83 10.04 41.25 - 27.48 - 13.83 1.91 Peanut shell ash 0.73 70.90 2.07 - - 0.62 22.29 - - loess 16.58 56.71 4.24 10.46 - 5.09 - 0.54 0.22 Cuttings 16.91 56.29 4.74 8.57 - 4.91 - 2.84 0.18

[0055] The chemical formula of the bonding component is (C6H 10 O5) 44 (C6H 10 O5) 22 (C5H 10 O4) 22 . (C6H 10 O5) 44 represents the glucose (Glc) unit, (C6H 10 O5) 22 represents the glucuronic acid (GlcA) unit, (C5H 10 O4) 22 represents the rhamnose (Rha) unit.

[0056] The common preparation method of the bonding component is to synthesize polysaccharides through enzyme catalysis reaction. The specific steps are as follows:

[0057] S1. Prepare raw materials: ensure that the ratio of D-glucose (Glc), L-rhamnose (Rha) and D-glucuronic acid (GlcA) is 2:1:1;

[0058] S2. Catalytic reaction: select transglycosidase, and mix D-glucose, L-rhamnose and D-glucuronic acid in proportion to promote the formation of a connection between them through a glycosidic bond.

[0059] The enzyme-catalyzed reaction has the following key steps: dissolving D-glucose, L-rhamnose and D-glucuronic acid in water, adding the transglycosidase in an amount of 0.5wt% of the total dry weight of the polysaccharide, and adjusting the pH value to 6.0; adding the transglycosidase to catalyze the reaction at a temperature of 40°C, wherein the enzyme catalyzes the formation of glycosidic bonds between glucose, rhamnose and glucuronic acid;

[0060] S3. Purification and molecular weight control: The reaction time is set to 60 h. After the reaction is completed, dialysis, gel permeation chromatography (GPC) or ultrafiltration technology is used to remove unreacted monosaccharides, enzymes and by-products to obtain a pure bonding component;

[0061] S4. Purification and molecular weight control: Drying and storage: The purified polysaccharide solution is freeze-dried to obtain a powdered bonding component.

[0062] The preparation process of the roadbed filler of the embodiment and the comparative example comprises the following steps:

[0063] Tunnel waste, curing agent and water are mixed and then molded and cured in sequence to obtain roadbed filling.

[0064] When the water is boiled to 100°C, the bonding component is added in advance and stirred with a liquid mixer until it is completely dissolved. At the same time, before adding water, ensure that the water temperature is maintained at 90°C.

[0065] In the present invention, with reference to the provisions of GB / T 50123-2019 "Standard for Geotechnical Test Methods", the diameter and height of the cured soil strength sample are 5 cm and 10 cm respectively, and it is prepared by static compression sampling method.

[0066] Then demoulding and curing: After demoulding, use a vernier caliper and an electronic scale to quickly test the size and quality of the sample. When the deviation between the diameter and height of the soil sample and the design value exceeds 1% or the deviation between the mass of the soil sample and the design value exceeds 1%, the soil sample is discarded and a new sample is made. Then put the soil sample that meets the requirements into a polyethylene sealed bag (to avoid water loss) and transfer it to a standard curing room (relative humidity 98%, temperature 23±1℃) for curing to the design age.

[0067] Test determination:

[0068] Examples 1-6 and Comparative Examples 1-3 were subjected to unconfined compression tests at curing ages of 7d and 28d, respectively, with reference to GB / T 50123-2019 "Standard for Geotechnical Test Methods", and immersed in distilled pure water at 27 days, and then subjected to water stability tests after continued curing for 24h.

[0069] Examples 1-6

[0070] Examples 1-6 are examples prepared based on a method for preparing low-permeability materials regenerated from tunnel waste solidified from a variety of solid wastes, as shown in Table 2.

[0071] Table 2 Specific implementation material dosage design scheme (dry mass ratio, dimensionless)

[0072]

[0073] Comparative Example 1

[0074] The curing agent in Comparative Example 1 is slaked lime used in on-site construction, and the components of the material are as follows: 1,200 parts of tunnel waste, of which 960 parts are loess, 240 parts are rock cuttings, and 100 parts are slaked lime.

[0075] Comparative Example 2

[0076] The tunnel waste in Comparative Example 2 does not contain rock cuttings, and the components of the material are as follows: 1200 parts of tunnel waste, of which 1200 parts are loess, 0 parts are rock cuttings, 58.3 parts are nickel-iron slag, 29.2 parts are blast furnace slag, 11.4 parts are carbide slag, 1.1 parts are phosphogypsum, 6 parts are steel slag, 14 parts are peanut shell ash, and 6 parts are bonding components.

[0077] Comparative Example 3

[0078] The curing agent in Comparative Example 3 does not contain a bonding component, and the components of the material are as follows: 1,200 parts of tunnel waste, of which 960 parts are loess, 240 parts are rock cuttings, 58.3 parts are nickel-iron slag, 29.2 parts are blast furnace slag, 11.4 parts are carbide slag, 1.1 parts are phosphogypsum, 6 parts are steel slag, and 14 parts are peanut shell ash.

[0079] Among the mechanical evaluation indicators in actual engineering, unconfined compressive strength is one of the most important indicators, and is a key indicator for judging whether the material meets the requirements of roadbed materials and whether it can be effectively used. Among them, the roadbed base, surface cover, and bottom liner need to be compacted during the construction process, so the compaction degree of the sample needs to be controlled indoors. In this implementation case, the compaction degree is controlled to be 96%. Table 3 is a comparison of the unconfined compressive strength of the cured and compacted samples of Examples 1-6 and Comparative Examples 1-3.

[0080] Table 3 Unconfined compressive strength test results of cured compacted specimens

[0081] Sample name 7-day unconfined compressive strength (MPa) 28-day unconfined compressive strength (MPa) Example 1 1.54 7.26 Example 2 1.67 7.83 Example 3 1.85 8.72 Example 4 2.12 10.75 Example 5 2.27 11.02 Example 6 2.38 13.05 Comparative Example 1 0.62 1.48 Comparative Example 2 1.05 5.35 Comparative Example 3 1.39 6.54

[0082] Table 2 shows the unconfined compressive strength test results of different curing formulas at 7 days and 28 days. The experimental results show that with the increase of curing time, the unconfined compressive strength of all samples is significantly improved. Among them, the 28-day unconfined compressive strength of Examples 1-6 is 7.26MPa, 7.83MPa, 8.72MPa, 10.75MPa, 11.02MPa and 13.05MPa, respectively, which is much higher than the 28-day unconfined compressive strength of Comparative Examples 1-3, which are 1.48MPa, 5.35MPa and 6.54MPa, respectively. These data show that the material obtained by the present invention has significant advantages in mechanical properties, especially under longer curing time, showing higher unconfined compressive strength.

[0083] Comparative analysis of Examples 1-6 shows that with the optimization of the curing agent formula, the unconfined compressive strength of the sample gradually increases, which indicates that the combination of the used gelling component, alkali-activated component, bonding component and reinforcing component has a significant synergistic effect. Among them, nickel-iron slag and blast furnace slag are used as gelling components. Under the action of alkali-activated components such as carbide slag and phosphogypsum, the gelling products generated by volcanic ash reaction significantly improve the strength of the material. At the same time, the active calcium, aluminum and silicon elements released by the reinforcing components peanut shell ash and steel slag further promote the hydration reaction and improve the density and strength of the material. In particular, Example 6 has an unconfined compressive strength of 13.05 MPa at 28 days, which indicates that under the optimal formula, the material has excellent mechanical properties and can fully meet or even exceed the engineering requirements of roadbed materials.

[0084] This paper uses tunnel waste as the main material and gives full play to its role as rock debris. First, rock debris, as coarse aggregate, together with other fine aggregates and solidified products, constitutes the skeleton structure of the material. This structure can effectively improve the density and overall mechanical properties of the material, and enhance its compressive strength and stability. The presence of aggregate can reduce the shrinkage of the solidified material during the hardening process and reduce the risk of cracking of the material, thereby ensuring its long-term durability. Secondly, rock debris does not exist only as an inert filler. In the alkaline environment provided by alkali-activated components such as carbide slag and phosphogypsum, certain chemical reactions may occur. In particular, when rock debris contains active silica and alumina, they can react with calcium hydroxide and other alkali-activated components to generate additional cementitious products such as calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH). The cementitious substances generated by these reactions fill the pores inside the material, further enhancing the density and compressive strength of the material.

[0085] The bonding component plays a vital role in the present invention. Its molecular chain contains a large number of hydroxyl and carboxyl groups. These functional groups can undergo physical or chemical adsorption with other components in the material (such as gelling components and alkali-excited components), thereby enhancing the mutual adhesion within the material. The hydroxyl group (-OH) has a strong hydrophilicity and can interact with the hydrogen bonds in water molecules and other hydrates to promote the hydration of the bonding component. This not only helps to stretch the molecular chain of the bonding component, but also can enhance the stability of the hydration product during the curing process, thereby helping to form a more solid network structure, thereby improving the overall strength of the material. The carboxyl group (-COOH) undergoes ion exchange reaction with cations (such as calcium ions, magnesium ions, aluminum ions, etc.) through its negative charge to form an ion cross-linked structure, thereby enhancing the strength of the material. During the curing process, the carboxyl group of the bonding component can react with calcium ions (Ca 2+), magnesium ions (Mg2+), etc. to form gel products such as calcium silicate hydrate (CSH), and cross-link with them, further improving the compressive strength of the material. In addition, the double helix structure of the bonding component gives it stability in high temperature and high strength environments. Due to its unique molecular structure, the bonding component can undergo stronger physical adsorption and chemical reactions with various components in the mixed waste (such as minerals in the waste residue), thereby enhancing the stability and strength of the solidified material.

[0086] During the solidification process of tunnel waste, the sulfate ions in the waste will change the pH value of the aqueous solution, which may affect the cementation reaction and thus the solidification process. However, the bonding component can effectively resist this influence through its network structure of hydrogen bonds and ionic bonds, maintaining the strength and stability of the material. In particular, the double helix structure of the bonding component can alleviate the adverse effects of the acidic environment on its gelation process to a certain extent, so that it can still maintain good stability in a strong acidic environment. In general, the structural characteristics of the bonding component enable it to exert excellent stability and strength in high temperature, strong acidic environment and strong sulfate soil, ensuring the excellent performance of the material under extreme conditions.

[0087] As a new type of low permeability material, its wide applicability in road mattress pads and landfill pads is improved. The permeability coefficient of the new low permeability material should be regarded as a key indicator. The present invention mainly verifies its permeability performance through flexible wall permeability experiments. The test results are shown in Table 4.

[0088] Flexible wall penetration was conducted according to ASTM D5084-10 and USEPA 1314, using GeotestTK2000 as the test instrument, with two parallel samples. The penetration test was set at an osmotic pressure of 50 kPa, a confining pressure of 55 kPa, and a hydraulic gradient of 100.

[0089] The steps of the flexible wall permeability test are as follows: ① Sample saturation. Take out the sample that has been cured to the design age (28d) from the curing room. Then put the sample into the saturator and place it in the vacuum saturation cylinder to complete the saturation. In this test, the soil sample is vacuumed for 8 hours at a vacuum negative pressure of -100kPa, and then injected with deionized water and left to stand for 4 hours. ② Sample installation. Take out the saturated soil, test its quality and calculate the saturation. Then put the sample into the latex membrane that matches the permeability tester and place it on the base of the permeability tester chamber. Permeable stone and glass fiber filter paper are placed between the sample and the base and top cover from bottom to top, and then the connection surfaces of the latex membrane and the base and top cover are sealed with water-stop rubber rings. Finally, after the top cover of the chamber is installed, it is connected to the permeability test control panel, and the permeability pressure and confining pressure are connected to the water pipe. ③ Test start. After the sample is installed, deionized water is injected into the permeability tester chamber, and a small confining pressure (3kPa) is applied to check the airtightness of the chamber. Then the confining pressure and osmotic pressure were increased to 55kPa and 50kPa respectively. The confining pressure and osmotic pressure were increased in a step-by-step manner at the same time, and the loading was completed within 2 minutes. During the permeation test, the exudate was collected in a conical bottle with a rubber stopper. ④ Calculation of permeability coefficient. After the test, the permeability coefficient of the sample was calculated based on the volume of the collected permeate.

[0090] Table 4 Results of the flexible wall penetration test of the solidified compacted samples

[0091] Sample name 28-day flexible wall penetration test (m / s) Example 1 <![CDATA[3.19×10 -8 ]]> Example 2 <![CDATA[5.46×10 -8 <!-- 8 -->]]> Example 3 <![CDATA[6.53×10 -8 ]]> Example 4 <![CDATA[5.32×10 -9 ]]> Example 5 <![CDATA[6.24×10 -9 ]]> Example 6 <![CDATA[7.15×10 -9 ]]> Comparative Example 1 <![CDATA[3.24×10 -6 ]]> Comparative Example 2 <![CDATA[1.28×10 -7 ]]> Comparative Example 3 <![CDATA[9.35×10 -7 ]]>

[0092] According to the results of the 28-day flexible wall permeability test in Table 3, low permeability materials show significant advantages in permeability. The following is an analysis of the reasons:

[0093] The gelling components of the present invention, nickel-iron slag and blast furnace slag, generate a large amount of gelling products, such as calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH), through a volcanic ash reaction under alkaline conditions. These gelling products have high compactness and adhesion, effectively fill the pores inside the material, and significantly reduce the permeability. The test results show that the permeability coefficients of the embodiments are all within 10 -8 -10 -9 The order of magnitude of m / s is due to the optimization of material ratio, which makes the density and pore filling effect of these samples reach the best.

[0094] In addition, the rock fragments in the tunnel waste in this paper effectively improve the permeability coefficient of the material through the synergistic effect with the gelling components and alkali-activated components in the curing agent. The good combination of rock fragments and the solidified product forms an excellent gradation, reduces the porosity inside the material, improves its density, and makes the material have lower permeability. In addition, the volume change of rock fragments is small, which can provide a stable skeleton structure during the solidification and hydration process of the material. This stable skeleton structure can prevent the material from increasing pores due to loosening or expansion of the internal structure, thereby ensuring that the material maintains low permeability during long-term use. The addition of rock fragments can also effectively fill the pore structure inside the material. Since rock fragments usually have irregular shapes and larger particle sizes, they can fill the larger pores between the gelling products and reduce the number and size of the connecting channels. Such a filling effect significantly reduces the flow path of water inside the material, thereby reducing permeability.

[0095] In addition, the bonding component is highly hydrophilic and can absorb water and swell to form a highly viscous gel-like substance. This gel-like substance can fill the tiny pores inside the material and significantly reduce the permeability of the material. By reducing the flow path of water and other fluids in the material, the bonding component enhances the material's resistance to penetration, making it more suitable for engineering applications that require high durability and impermeability.

[0096] The present invention significantly improves the material's impermeability. By using bonding components and multi-solid waste to synergistically improve the material's impermeability, the three-dimensional network formed by the bonding components works together with the hydration products of blast furnace slag and nickel-iron slag to fill the tiny pores in the material and reduce the porosity. Small particle fillers such as blast furnace slag and phosphogypsum form an excellent gradation relationship with tunnel waste. The permeability coefficient after 28 days is 3.19×10 -8 -7.15×10 -9 m / s, far exceeding the original lime-based solidified cementitious materials.

[0097] Further, the mechanical properties of the material are significantly improved, and the unconfined compressive strength of the tunnel waste slag recycling material is significantly improved by optimizing the curing agent formula. The ferronickel slag and blast furnace slag, under the action of alkali-excited components (carbide slag and phosphogypsum), the gelled products generated by the volcanic ash reaction greatly improve the strength of the material. The active calcium, aluminum, and silicon elements released by the reinforcing components (peanut shell ash and steel slag) further promote the hydration reaction and improve the density and mechanical properties of the material. In particular, in Example 6, the unconfined compressive strength of 28 days reaches 13.05MPa, indicating that the material can meet the engineering requirements of the roadbed material. In addition, rock fragments not only improve the density and compressive strength of the material as aggregate, but also participate in chemical reactions in an alkaline environment to generate additional gelled products, further enhancing the performance of the material. The bonding component improves the overall bonding and strength of the material by forming a network structure with the hydration product.

[0098] The curing agent achieves resource recycling by utilizing industrial by-products such as nickel-iron slag, blast furnace slag, carbide slag, phosphogypsum, steel slag and peanut shell ash, has good environmental friendliness and reduces raw material costs; the curing agent components are diverse and synergistic, and can adapt to different construction environments and material requirements, especially in projects that require high impermeability and high durability.

[0099] During the hydration reaction, the reinforcing components (peanut shell ash and steel slag) continuously release active calcium, aluminum and silicon elements, maintaining and promoting the continuous progress of the hydration reaction, thereby improving the strength and durability of the cured material.

[0100] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0101] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A curing agent, comprising a gelling component, an alkali-activated component, a bonding component, and a reinforcing component, characterized in that: The mass ratio of the gelling component, the alkali-activated component, the bonding component and the reinforcing component is: (6-7): 1: (0.45-0.7): (1.6-1.7), The bonding component is composed of repeated tetrasaccharide units, which include D-glucose, D-glucuronic acid, D-glucose and L-rhamnose connected in sequence, wherein the D-glucose and D-glucuronic acid are connected by β-1,4 glycosidic bonds, and the L-rhamnose and D-glucose are connected by α-1,3 glycosidic bonds to form a double helix structure.

2. The curing agent according to claim 1, characterized in that The molecular formula of the bonding component is (C6H 10 O5) n (C6H 10 O5) m (C5H 10 O4) k , where (C6H 10 O5) n is a glucose unit, (C6H 10 O5) m is a glucuronic acid unit, (C5H 10 O4) k It is a rhamnose (Rha) unit, wherein the values ​​of n, m and k are 20-25, and n, m and k satisfy 2:1:1, the average molar mass of the bonding component is not less than 500000 g / mol, and the particle size is not greater than 0.15 mm.

3. The curing agent according to claim 2, characterized in that The bonding component is prepared from D-glucose, L-rhamnose and D-glucuronic acid under the catalytic action of transglycosidase, the added amount of the transglycosidase is 0.1wt%-0.8wt% of the total dry weight of D-glucose, L-rhamnose and D-glucuronic acid, the reaction pH is 5.5-7.0, the reaction temperature is 30°C-50°C, and the reaction time is 48h-72h.

4. The curing agent according to claim 3, characterized in that The cementitious material is composed of nickel-iron slag and blast furnace slag, and the mass ratio of the nickel-iron slag to the blast furnace slag is (2-3):

1.

5. The curing agent according to claim 4, characterized in that The alkali-activated material consists of carbide slag and phosphogypsum, and the mass ratio of the carbide slag to the phosphogypsum is (10-11) / 1.

6. A tunnel waste slag regeneration low permeability material based on solidification of various solid wastes, comprising the curing agent according to any one of claims 1 to 5, characterized in that: It also includes tunnel slag and water, wherein the dry mass ratio of the tunnel slag to the curing agent is 1:(0.08-0.1), the moisture content of the tunnel slag is controlled at 15%-16%, the curing agent includes a gelling component, an alkali-activated component, a bonding component, and a reinforcing component, and the mass ratio of the gelling component, the alkali-activated component, the bonding component, and the reinforcing component is: (6-7): 1:(0.45-0.7):(1.6-1.7), The bonding component is composed of repeated tetrasaccharide units, which include D-glucose, D-glucuronic acid, D-glucose and L-rhamnose connected in sequence, wherein the D-glucose and D-glucuronic acid are connected by β-1,4 glycosidic bonds, and the L-rhamnose and D-glucose are connected by α-1,3 glycosidic bonds to form a double helix structure.

7. The material according to claim 6, characterized in that 80%-85% of the tunnel waste is loess, and 15%-20% is basalt rock fragments. According to the liquid limit and plastic limit combined determination test, the liquid limit is 29.2% and the plastic limit index is 10.9, which is low plastic clay.

8. The material according to claim 7, characterized in that The total amount of soluble salt in the tunnel waste is 3.0%-3.1%, the total amount of chloride ions is 0.20%-0.30%, and the concentration of sulfate ions is 1.10%-1.30%, which belongs to strong sulfate soil. 2- ) / c(Cl - )>2.

9. The material according to claim 8, characterized in that The sulfate ion leaching concentration of the tunnel waste is 1701 mg / L-1758 mg / L.

10. A method for preparing the material according to any one of claims 6 to 9, characterized in that: Includes steps: Tunnel waste, curing agent and water are mixed and then molded and cured in sequence to obtain a material for roadbed filling.

Citation Information

Patent Citations

  • Masonry cement having higher strength and water retention

    CN101182139A

  • Permeable recycled aggregate and ceramsite concrete doped with industrial and agricultural solid waste and preparation

    CN104478361A

  • Enhanced fermentation process using a transglycosidase

    CN105874076A

  • Conditioning agent for converting energy to supply fertilizer and increasing soil fertility and preparation method and application thereof

    CN106831170A

  • Internal doping type concrete compaction reinforcing agent and preparation method thereof

    CN117886535A